Penerapan Teknologi Digital Marketing Untuk Meningkatkan Strategi Pemasaran Pada UMKM Cendol Di Kelurahan Kauman Kota Blitar - Ratna Melinda Putri; Eko Purwanto (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
UMKM Cendol Sueger is a Micro, Small and Medium Enterprises (UMKM) engaged in the business of cendol production drinks located in the Kauman sub-district, Kepanjen Kidul District, Blitar City. The problem faced by Cendol Sueger SMEs is that their marketing activities are still very minimal and traditional. For this reason, it is necessary to provide training on the importance of implementing digital marketing so that the marketing system can be better so that it can expand the scope of its business targets and can support even better sales activities. The purpose of this research is to apply digital marketing to improve the marketing strategy of Cendol Sueger SMEs. Some of the digital e-commerce and social media used are grab, website, and Instagram accounts. The results of the study show that Cendol Seger MSMEs now understand and are able to create accounts, manage and utilize social media to expand their marketing reach online so that they can improve marketing strategies and sales results for Cendol Sueger MSMEs.